Investigation of the Mouse Infection Model for Echovirus 18 - Xiang, Lei; Zhai, Linlin; Ou, Guanyong; Zhao, Wei; Yang, Yang; Shen, Chenguang (Viruses, 2025)
Echovirus 18, a member of the B group of enteroviruses, is a significant etiological agent of aseptic meningitis and viral encephalitis in children. In this study, we investigated the pathogenicity of E18 by establishing a mouse infection model after comparing various mouse strains and injection methods. Two-day-old IFNAR1 knockout mice infected with clinical isolates of E18 exhibited symptoms such as lethargy, hind limb paralysis, and even mortality. Similarly, some two-day-old C57BL/6J mice displayed comparable symptoms; however, the incidence was lower than that observed in IFNAR1 knockout mice. No similar symptoms were noted in any Balb/c mice. Significant pathological changes were observed in skeletal muscle, brain tissue, and other organs of symptomatic mice; among these tissues, skeletal muscle demonstrated the highest viral load. The established infection model using two-day-old IFNAR1 knockout mice provides valuable insights into further investigations regarding its pathological injury mechanisms as well as the protective effects conferred by antibodies.